The degree of possession of mathematics teachers in the governorates of South Al-Batinah and Al-Dakhiliyah in the Sultanate of Oman of the concepts of artificial intelligence, its applications and their attitudes towards it - Al-Jadeedi, Kothar Khalfan; Al-Riyami, Mohammad Nassir; Al-Mazidi, Nassir Salim; Al-Saqri, Mahmood Nassir (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to identify the degree of possession of mathematics teachers in the governorates of South Al Batinah and Al Dakhiliyah in the Sultanate of Oman of the concepts of artificial intelligence, its applications and their attitudes towards it, and to identify the most important challenges facing teachers in using artificial intelligence applications in education. The researcher used the descriptive approach, as she relied on two tools in this study: the test and the questionnaire, and the Statistical Package for Social Sciences (SPSS) program was used to analyze the results. The study sample consisted of (297). The results of the research concluded that the degree of teachers’ possession of artificial intelligence concepts was low, and in contrast, females had higher possession of the concepts than males, while there were no statistically significant differences attributable to the variables of years of experience and educational governorate in the degree of teachers’ possession of artificial intelligence concepts. The results also indicated that teachers’ positive attitudes towards employing artificial intelligence applications in learning were high, and the results also showed that there was agreement among teachers on the existence of challenges in employing artificial intelligence applications and were high. The study presented several recommendations, including including teacher preparation programs in colleges of education in the field of employing artificial intelligence applications, and preparing the infrastructure of schools, including devices and Internet networks, to employ artificial intelligence applications.